Legal Analysis on the Seaworthiness of High-Speed Passenger Ships (HSC) and Challenges in Shipping Safety Supervision in the Waters of the Riau Islands: Research Study at Sekupang Domestic Port (International Journal of Education and Literature, 2024)
This research is based on the importance of shipping safety to protect passengers, crew, and the maritime environment from high risk of accidents, especially on high-speed ships that have special operational characteristics. Legal arrangements related to HSC seaworthiness have been regulated in various national regulations such as Law Number 17 of 2008 concerning Shipping, Regulation of the Minister of Transportation Number PM 12 of 2022, as well as international conventions such as SOLAS, MARPOL, and STCW. However, its application in the field still faces various obstacles. This study aims to analyze the law regarding the seaworthiness of high-speed passenger ships (HSC) and challenges in the supervision of shipping safety in the waters of the Riau Islands, with a focus on the study at Sekupang Domestic Port, Batam City. This study uses normative juridical methods to analyze applicable laws and regulations and empirical sociological methods to explore field information through interviews and observations of related parties, such as port authorities, ship operators, and crew members at Sekupang Domestic Port. The results of the study show that the implementation of HSC seaworthiness in the waters of the Riau Islands is not optimal. The main obstacles include a lack of trained human resources, inadequate inspection facilities, weak law enforcement, ineffective inter-agency coordination, and low awareness and education on the importance of maritime safety. Based on these findings, it is recommended that the Batam Special KSOP improve the competence of inspectors and supervisors through a continuous training program. The government is expected to allocate a budget for investment in modern inspection facilities and equipment. In addition, the maritime community, especially operators and crew members, need to increase their awareness and understanding of shipping safety through active participation in education and training programs. With these efforts, it is hoped that the implementation of HSC seaworthiness can be more optimal, thereby improving shipping safety in the waters of the Riau Islands.